Pengaruh Teknik Pembelajaran Aktif Terhadap Prestasi Akademik Siswa: Analisis Literatur Komprehensif - Sarudin Sarudin; Muhammad Mahfud; Muhammad Fuad; Puspita Dian Agustin; Muhammad Fadli (Jurnal Ilmiah Edukatif, 2024)
This study aims to analyse the effect of active learning techniques on students' academic achievement through a comprehensive literature review. Active learning techniques, which include methods such as group discussion, simulation, and hands-on practice, are reported to improve students' understanding of subject matter as well as their learning motivation. The research method in this review uses the literature method. The results of the literature review show that students who engage in active learning processes gain a deeper understanding and are able to apply the concepts learnt more effectively compared to traditional learning methods. In addition, this technique is also proven to improve students' critical and analytical thinking skills, which has a positive impact on their academic performance. Based on these findings, it is recommended that active learning techniques be integrated into the educational curriculum to encourage maximum academic achievement and the development of essential skills for students.